Social anxiety in the eating disorders: a systematic review and meta-analysis. Issue 15 (10th April 2018) - Kerr-Gaffney, Jess; Harrison, Amy; Tchanturia, Kate
Abstract: Social anxiety disorder is one of the most common comorbid conditions in eating disorders (EDs). The aim of the current review and meta-analysis is to provide a qualitative summary of what is known about social anxiety (SA) in EDs, as well as to compare levels of SA in those with EDs and healthy controls. Electronic databases were systematically searched for studies using self-report measures of SA in ED populations. In total, 38 studies were identified, 12 of which were included in the meta-analyses. For both anorexia nervosa (AN) and bulimia nervosa, there were significant differences between ED groups and HCs, with medium to large effect sizes. Findings from the qualitative review indicate that levels of SA are similar across the ED diagnoses, and SA improves with treatment in AN. In addition, high levels of SA are associated with more severe ED psychopathology, but not body mass index. These findings add to the wider literature on socio-emotional functioning in EDs, and may have implications for treatment strategies.